Labeling and preliminary in vivo assessment of niobium-labeled radioactive species: A proof-of-concept study - Radchenko, V; Bouziotis, P; Tsotakos, T; Paravatou-Petsotas, M; la Fuente, A; Loudos, G; Harris, A; Xanthopoulos, S; Filosofov, D; Hauser, H; Eisenhut, M; Ponsard, B; et al. (Elsevier, 2016)
The application of radionuclide-labeled biomolecules such as monoclonal antibodies or antibody fragments for imaging purposes is called immunoscintigraphy. More specifically, when the nuclides used are positron emitters, such as zirconium-89, the technique is referred to as immuno-PET. Currently, there is an urgent need for radionuclides with a half-life which correlates well with the biological kinetics of the biomolecules under question and which can be attached to the proteins by robust labeling chemistry. 90Nb is a promising candidate for in vivo immuno-PET, due its half-life of 14.6 h and low β+ energy of Emean = 0.35 MeV per decay. 95Nb on the other hand, is a convenient alternative for longer-term ex vivo biodistribution studies, due to its longer half-life of (t1/2 = 35 days) and its convenient, lower-cost production (reactor-based production). In this proof-of-principle work, the monoclonal antibody bevacizumab (Avastin®) was labeled with 95/90Nb and in vitro and in vivo stability was evaluated in normal Swiss mice and in tumor-bearing SCID mice. Initial ex vivo experiments with 95Nb-bevacizumab showed adequate tumor uptake, however at the same time high uptake in the liver, spleen and kidneys was observed. In order to investigate whether this behavior is due to instability of *Nb-bevacizumab or to the creation of other *Nb species in vivo, we performed biodistribution studies of 95Nb-oxalate, 95Nb-chloride and 95Nb-Df. These potential metabolite species did not show any specific uptake, apart from bone accumulation for 95Nb-oxalate and 95Nb-chloride, which, interestingly, may serve as an "indicator" for the release of 90Nb from labeled biomolecules. Concerning the initial uptake of 95Nb-bevacizumab in non-tumor tissue, biodistribution of a higher specific activity radiolabeled antibody sample did show only negligible uptake in the liver, spleen, kidneys or bones. In-vivo imaging of a tumor-bearing SCID mouse after injection with 90Nb-bevacizumab was acquired on an experimental small-animal PET camera, and indeed showed localization of the radiotracer in the tumor area. It is the first time that such results are described in the literature, and indicates promise of application of 90Nb-labeled antibodies for the purposes of immuno-PET.